Spectroscopy of (4) lattice gauge theory with = 3 antisymmetric fermions - Ed Bennett (Proceedings of The 39th International Symposium on Lattice Field Theory — PoS(LATTICE2022), 2023)
We perform numerical calculations of masses and decay constants of the lightest (flavoured) pseu- doscalar, vector and axialvector mesons in the (4) lattice gauge theory with three Dirac fermions in the antisymmetric representation. The corresponding continuum theory plays an important role in certain ultra-violet complete realisations of composite Higgs, partial top compositeness, and composite dark matter models. In addition, we measure the masses of other flavoured mesons in spin-0 and 1 channels, as well as the first excited state of the vector mesons. Using the gradient flow to set the scale, we carry out the continuum extrapolation and show preliminary results for the meson spectrum of the theory.